KAJIAN ASPEK SOSIAL, EKONOMI, LINGKUNGAN DAN KEBERLANJUTAN PROGRAM CSR UNTUK DESTINASI WISATA KAMPUNG TERIH BATAM - Amalia, Eva; Abnur, Asman (JURNAL MATA PARIWISATA, 2023)
ABSTRACT This research aims to evaluate the social, economic, environmental, and sustainability aspects of the Corporate Social Responsibility (CSR) program implemented in the tourist destination of Kampung Terih. The study also addresses the challenges faced during the CSR implementation, particularly within the context of empowering coastal communities and fishermen. Empowering the community in Kampung Terih through the CSR program is a primary strategy in achieving sustainable development. This research employs a qualitative descriptive approach to provide a detailed examination of the strategies and CSR programs implemented by companies, with a specific focus on community empowerment. This approach pays special attention to the potential of natural resources and human resources in Kampung Terih, aiming to enhance the success of empowerment programs. Success indicators for the empowerment of fishermen groups, including economic, social, and environmental aspects, serve as the main guidelines in the implementation of CSR programs in Kampung Terih. It is anticipated that this initial initiative, directly targeting the fishermen groups, will make a significant contribution to the development of the tourism destination, particularly in the context of ecotourism in Kampung Terih. The implementation of this program is expected to create sustained positive impacts in economic, social, and environmental aspects. Keywords: csr, economic, environment, implementation, social, sustainability